The Development of Agrotourism Areas As A Regional Approach And The Empowerment Of Parepare Community - Arifuddin, Arifuddin; Ambar, Abdul Azis; Irmayani, Irmayani; S, Syafrianto (Agrikan: Jurnal Agribisnis Perikanan, 2021)
The development of the tourism sector has sufficient opportunities because apart from being one of the producers of tourism economic growth, the tourism sector is also expected to have the opportunity to support the other of development sectors, such as the plantation sector, agriculture, industrial trade and others.This study aims to analyze the condition of the development of agro-tourism areas as a regional approach and alternative empowerment of farmer communities atParepare City in the development process of the agro-tourism area. The technique of collecting data was through direct observation, conducting interviews that involve 80 respondents. The analysis used in this studywas descriptive qualitative. The method used in analyzing the data was the SWOT analysis.The results showed that the Internal-External matrix produces a strategy in quadrant I position. Quadrant I was a very favorable condition because it has opportunities and strengths.